Analysis and Control of an Unstable Mode in a Combustor with Tuneable End Condition. (September 2013) - Heckl, Maria; Kosztin, Béla
A major problem in the development of low-pollution combustion systems are thermo-acoustic instabilities, i.e. large-amplitude oscillations generated by a feedback between the unsteady heat release and acoustic waves. In order to develop robust control strategies, it is necessary to have a predictive model that captures the physics of the phenomenon. The aim of this paper is to present such a model for a dump combustor with a generic heat release law, and fitted at the inlet end with a perforated plate backed by a tuneable cavity. Our model leads to a simple governing equation for one acoustic mode in the combustor, and from this equation stability predictions can be made with a minimum of numerical effort. We will use it to examine the effect of various system parameters.